Evaluation of Çanakkale Kilitbahir Castle in the Context of Refunctioning - Kubra Duyar; Yasemin Kucukgok; Meltem Duman Akyildiz (Journal of Contemporary Urban Affairs, 2018)
The Dardanelles Strait functions as a bridge between Biga and Gelibolu peninsulas, connecting the Aegean Sea and the Marmara Sea. Many defences have been built on the Dardanelles Strait, which has hosted many civilizations from the past to the present day, in line with the needs of the time. Kilitbahir Castle, which has a three-leaf clover plan and is located on a slope rising on the Gallipoli peninsula in the narrowest part of the Bosphorus after the conquest of Istanbul by Mehmet the Conqueror; manifests itself as a pioneering structure of the military architecture of the era with the developing artillery technology. In terms of protecting the physical environment, it is observed that the defensive buildings which survived up to today are not adequately protected, losing their historical and architectural values. In this context, the restoration of Kilitbahir Castle dating back to Ottoman Period defence structures on the Dardanelles Strait was evaluated. Its phases throughout the process along with the current location and architecture were evaluated by using written and visual resources. European Archives, BNF Archives, Topkapi Palace Archives and Istanbul University Archives were utilized for reaching the castle engravings. In accordance with the information obtained in the historical research process, the exhibition arrangement and environment planning project of the structure, which serves as a museum, was prepared.